Root-applied glycinebetaine decreases nitrate accumulation and improves quality in hydroponically grown lettuce. (1st January 2022) - Jokinen, Kari; Salovaara, Anna-Kaisa; Wasonga, Daniel O.; Edelmann, Minnamari; Simpura, Ilkka; Mäkelä, Pirjo S.A.
Highlights: Nitrate in lettuce leaves is often associated with harmful effects on human health. Glycinebetaine (GB) in a fertigation solution was taken up by and translocated in leaves. Lettuce nitrate content was decreased by GB in a concentration-dependent manner. GB supplement in hydroponics increased lettuce leaf dry matter content. GB fortification improved the edible and nutritional value of lettuce. Abstract: Leafy vegetables like lettuce ( Lactuca sativa L.) naturally have high nitrate content and the European Commission has set maximum level for nitrate in lettuce. Glycinebetaine is an organic osmolyte alleviating plant stress, but its role in leaf nitrate accumulation remains unknown. The uptake of glycinebetaine by lettuce roots, and its potential to regulate lettuce nitrate content and improve plant quality were investigated. Two hydroponic lettuce experiments were conducted with different glycinebetaine application rates (Exp1: 0, 1, 7.5, and 15 mM; Exp2: 0, 1 + 1 + 1, 1 + 10, and 4 mM). Plants were analyzed at varying time points. Root application resulted in glycinebetaine uptake and translocation to the leaves. Glycinebetaine concentrations > 7.5 mM reduced leaf nitrate up to 40% and increased leaf dry matter content. Glycinebetaine showed a positive effect on leaf mineral and amino acid composition. Thus, glycinebetaine could be a novel strategy to reduce the nitrate content in hydroponic lettuce.